Extraction optimization of bioactive compounds from Thymus ulgaris L.: comparison of heat-assisted and ultrasound-assisted extractions - Caleja, Cristina (2022)
Plants have been used since ancient times due to their biological action associated mainly with several phytochemicals, including phenolic compounds1. Thymus vulgaris L. is a species described as a potential source of natural molecules with applications in the food industry, but also in the cosmetic and pharmaceutical industry due to its antibacterial, antifungal, and anti-inflammatory effects2. In this sense, the present study aimed to compare extraction systems in terms of phenolic compounds from T. vulgaris through the heat-assisted (HAE) and ultrasound-assisted extraction (UAE) techniques, aiming to improve its potential for industrial applications. For this propose, an extraction optimization was studied using three independent variables, time (t, minutes), solvent (S, % of ethanol), and temperature (T, ºC) or power (P, W), in a three-level Box-Behnken design, analyzing the surface methodology (RSM). The extraction yield and the content in phenolic compounds identified by HPLC-DAD-ESI/MS were the experimental responses applied. The polynomial models were successfully fitted to the experimental data and used to determine the optimal HAE and UAE conditions. Nineteen phenolic compounds were identified, nine of which were phenolic acids (mainly caffeic acid derivatives) and ten flavonoids: flavan-3-ols (catechin derivatives), flavones (quercetin derivatives), flavonols (apigenin and luteolin derivatives) and flavanones (eriodictyol derivatives). The conditions obtained for the optimal extraction of phenolic compounds, that allowed the experimental validation of the predictive model are 3% ethanol (v/v) for 89 minutes at a temperature of 98º C for HAE and 77% ethanol (v/v) for 17 minutes at 207 W for UAE. Extraction optimization is important from an industrial point of view, as it allows obtaining extracts with a high content of bioactive compounds. Considering that the phenolic composition appears in literature as a direct influence on bioactive properties, the optimization processes will allow a better exploitation of extracts, ensuring the greatest cost reduction for the industry.